Sexta Bienal de La Habana : el individuo y su memoria. - Bienal La Habana 1997; Abascal, Ibis Hernandez; Achugar, Hugo; Adipurnomo, Nindityo; Aguilera, Dodanys M. Garcia; Aleixo, Ricardo; Alexis, Gerald; Almada, Adriana; Alvarez, Lupe; Amor, Mónica; Arahmaiani; Araque, William Nino; et al. (Paris : L'Association Française d'Action Artistique, 1997)
Adipurnomo, Nindityo ; Almeida, Lourdes ; Alom, Juan Carlos ; Altamirano, Carlos ; Alvarez, Esso ; Alvim, Fernando ; Alvisa, Lidzie ; Anderson, Laura ; Ankomah, Owusu ; Antunes, Arnaldo ; Apóstol, Alexander ; Aquilizan, Alfredo Juan ; Arahmaiani ; Aranovich, Claudia ; Arellano, Agnes ; Bárcenas, Eduardo ; Barreto, Lia Menna ; Bastista, José Angel Toirac ; Bedoya, Juan Enrique ; Bejarano, Agustin ; Benedit, Luis Fernando ; Beng-Thi, Jack ; Benjamin, Mario ; Benski, Kuki ; Betote, Bill Akwa ; Bidjocka, Bili ; Binder, Pat ; Biswas, Sutapa ; Boltanski, Christian ; Bony, Oscar ; Boxer, David ; Bravo, Patricia ; Camp, Sokari Douglas ; Canas, Germán Martinez ; Carrié, Edouard Duval ; Casas, Francisco ; Chandrasekaran, S. ; Chiriboga, Lucia ; Conde, Pablo ; Conte, Guillermo ; Costi, Rochelle ; Cruise, Wilma ; Dimitrijevic, Braco ; Driss, Hichem ; Duclos, Arturo ; Ennadre, Touhami ; Estévez, Carlos ; Facey, Laura ; Fiallo, Gloria ; Flemming, Alex ; Fors, José Manuel ; Freiberger, Angela ; Frigerio, Ismael ; Gallardo, Carlos ; Garaicoa, Carlos ; Garcia, Daniel ; Gaye, Amadou ; Geiger, Anna Bella ; Ghomes, Rogerio ; Goldwasser, Gerardo ; Goulart, Claudio ; Hazoumé, Romuald ; Heyleger, Glenda ; Huarcaya, Roberto ; Irigoyen, Rosa ; Iturria, Ignacio ; Jaramillo, Edith Arbeláez ; Jaramillo, Jenny ; Jorge, Yamilys Brito ; Juliet, Reamillo and ; Katz, Leandro ; Kcho ; Kentridge, William ; Kogut, Sandra ; Koraichi, Rachid ; Laignelet, Victor ; Langa, Moshekwa ; Lanzarini, Ricardo ; Latamie, Marc ; Lemebel, Pedro ; Longo, Dora ; López, Elvis ; López, Marcos ; Lovell, Whitfield ; Machado, Oscar ; Manik, Andar ; Marino, Armando ; Marintan, Sirait ; Martinez, César ; Mateos, Sol ; McCarthy, Anamaria ; Médici, Eduardo ; De Mello, Vicente ; Mendive Hoyo, Manuel ; etc.
biografie
Spaans
Spaans & Frans
boek